Bicuspid valve repair outcomes are improved with reduction and stabilization of sinotubular junction and annulus with external annuloplasty - Shraer, Nathanael; Youssefi, Pouya; Zacek, Pavel; Debauchez, Mathieu; Leprince, Pascal; Raisky, Olivier; Lansac, Emmanuel (The Journal of thoracic and cardiovascular surgery, 2024)
OBJECTIVE: We investigated long-term outcomes of bicuspid aortic valve (BAV) repair, with external annuloplasty, according to aorta phenotype. METHODS: Between 2003 and 2020, all patients with BAV operated on for aortic insufficiency (AI) and/or aneurysm were included. Repairs included isolated AI repair with subvalvular with or without sinotubular junction (STJ) (single or double) annuloplasty, supracoronary aorta replacement (with or without hemiroot remodeling), and root remodeling with external subvalvular ring annuloplasty. RESULTS: Among 343 patients operated, reparability rate was 81.3% (n = 279; age 46 ± 13.3 years). At 10 years (median follow-up: 3.42 years; interquartile range, 1.1, 5.8), survival was 93.9% (n = 8 deaths, similar to general population), cumulative incidence of reoperation was 6.2% (n = 10), AI grade >2 was 5.8% (n = 9), and grade >1 was 23.0% (n = 30). BAV repair stabilizing both the annulus and STJ with annuloplasty, compared with nonstabilized STJ repair (single annuloplasty), had lower incidence of reoperation (2.6% vs 22.5%, P = .0018) and AI grade >2 (1.2% vs 23.6%, P < .001) at 9 years. Initial commissural angle <160° was not a risk factor for reoperation, compared with angle ≥160° if symmetrical repair was achieved (2.7% and 4.1%, respectively, at 6 years, P = .85). Multivariable model showed that absence of STJ stabilization (odds ratio, 6.7; 95% confidence interval, 2.1-20, P = .001) increased recurrent AI, but not initial commissural angle <160° (odds ratio, 1.01; 95% confidence interval, 0.39-2.63, P = .98). Commissures adjusted symmetrically led to lower transvalvular gradient, compared with nonsymmetrical repair (8.7 mm Hg vs 10.2 mm Hg, P = .029). CONCLUSIONS: BAV repair, tailored to aorta phenotype, is associated with excellent durable outcomes if both annulus and STJ are reduced and stabilized with external ring annuloplasty. Commissural angle <160° is not associated with reoperation if symmetrical repair is achieved.
Keywords: aortální aneurysma; dospělí; Cardiac Valve Annuloplasty; bicuspid aortic valve; bikuspidální aortální chlopeň; Female; Heart Valve Prosthesis Implantation; anuloplastika srdeční chlopně; aortální chlopeň; Adult; aortic valve repair; výsledek terapie; ženské pohlaví; aortic insufficiency; chirurgická náhrada chlopně; Time Factors; časové faktory; lidé; aortální insuficience; Aortic Valve Insufficiency; pooperační komplikace; Bicuspid Aortic Valve Disease; Treatment Outcome; annuloplasty; Reoperation; Risk Factors; reoperace; retrospektivní studie; Male; Postoperative Complications; aortic aneurysm; rizikové faktory; Aortic Valve; lidé středního věku; mužské pohlaví; Retrospective Studies; Middle Aged; Aortic Aneurysm; Humans